Social learning environment and problem-solving technique on science education university students’ attitudes: does gender moderate the relationship? / Obikezie Maxwell Chukwunazo ... [et al.] - Obikezie, Maxwell Chukwunazo; Egolum, Evelyn Obianuju; Enebechi, Regina Ijeamasi; Okafor-Agbala, Uzoamaka Chimuanya; Abumchukwu, Adanna Angela; Chikendu, Rebecca Ebonam; Ekoyo, Destiny Onyebuchi; Anulika, Eke Joy; Fadekemi, Awosika Opeyemi; Onyeka, Edith Chinyere (Universiti Teknologi MARA, 2025)
This investigation evaluated the social learning environment and problem solving technique on Science Education university students’ (n=909) attitudes: do gender moderate the relationship? The study area is federal universities in Enugu and Ebonyi state, Nigeria. The methodology used in the study was correlation design. The Yamane sample size technique was used to draw the sample. The study was guided by four research questions and four hypotheses. The Social Learning Environment Questionnaire (SLEQ), the Problem Solving Techniques Inventory (PSTI), and the Student's Attitude Scale (SAS) were the three instruments used in data collection. The results indicated that attitudes about Science Education option courses and perceptions of the social learning environment among university students were moderate positively related (R=0.330), the relationship is significant (P < .05). More so, the result indicated that attitudes about Science Education option courses and perceptions of the social learning environment among university male students were low positively related (R = 0.039). However, there is a significant difference in relationship (P <.05). The result also revealed that attitudes about Science Education option courses and perceptions of the social learning environment among university female students were moderate positively related (R = 0.459), however, a significant difference exists in the relationship (P > .05). It is also revealed that there is a low positive relationship between university students’ problem- solving techniques and attitude towards Science Education option subjects scores. (R= 0.171), thus there is a significant difference in relationship (P <.05). Finally, attitudes about Science Education option courses and problem-solving techniques among university male and female students were low positively. (R= 0.132 male; R = 0.258 female). As a result, the relationship is significant (P <.05).